The treatment of cementitious surface by selected silicate sealers. Issue 1 (1st September 2022) - Iliushchenko, V; Kalina, L; Hruby, P; Jr, V Bilek; Fladr, J; Bily, P; Bojanovsky, J
Abstract : Over the past decades, the efficiency of the silicate-based surface treatment agents, in other words, sealers, in concrete systems has been widely investigated. The surface treatment technology protects the cementitious systems against the penetration of undesirable substances. Nevertheless, understanding of the several aspects concerning silicate-based sealers is not entirely clear. This paper studies the action mechanism of selected silicates such as potassium, sodium, lithium water glasses, and colloidal silica. The effectiveness of used sealers in terms of water absorption reduction, the ability of silicates to heal pores, and the influence on the microstructure of the cement substrate were studied. Instrumental methods such as rheology, mercury intrusion porosimetry, or scanning electron microscopy were used to achieve satisfactory results. Nuances between the unique film-forming sealers were found. Colloidal silica showed a low sealing effect compared to alkali silicates.